ChemInform Abstract: A Dual‐Catalysis Approach to the Kinetic Resolution of 1, 2‐Diaryl‐1, 2‐diaminoethanes. Issue 10 (7th March 2013) - Min, Chang; Mittal, Nisha; De, Chandra Kanta; Seidel, Daniel
Abstract A combination of achiral N, N‐dipropylaminopyridine with a chiral 1, 2‐cyclohexanediamine derivative is tested as a catalytic system for the kinetic resolution of diamines (I).